2011
DOI: 10.1592/phco.31.9.871
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Hospitalwide Increase in Empiric Pediatric Vancomycin Dosing on Initial Trough Concentrations

Abstract: Study Objective To evaluate the impact of a hospital-wide increase in the recommended vancomycin starting dose in children from 45 to 60 mg/kg/day on vancomycin trough concentrations. Design Retrospective chart review. Setting Dedicated children's hospital located within a tertiary care, academic medical center. Patients Children aged 1 month-12 years with normal renal function who were treated with vancomycin during two one-year periods: July 2006-June 2007 (low dose [LD]; 45 mg/kg/day divided q8 hour; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 17 publications
4
34
2
1
Order By: Relevance
“…At this moment, several pediatric pharmacokinetic models of vancomycin have been published (19-34, 36, 54-59), but only few individualized, model-based dosing algorithms are available (25,27,30,34,57,59). In clinical practice, target concentrations and AUC 24 /MIC values are hard to achieve (42)(43)(44)(45)60). Simulations based on two models (22,23), that are now validated internally and externally, showed, indeed, that adapted doses are needed, especially for neonates and young infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this moment, several pediatric pharmacokinetic models of vancomycin have been published (19-34, 36, 54-59), but only few individualized, model-based dosing algorithms are available (25,27,30,34,57,59). In clinical practice, target concentrations and AUC 24 /MIC values are hard to achieve (42)(43)(44)(45)60). Simulations based on two models (22,23), that are now validated internally and externally, showed, indeed, that adapted doses are needed, especially for neonates and young infants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of proposed vancomycin dosing regimens currently available for neonates and infants (10,11,(37)(38)(39)(40)(41), studies reporting on the results of therapeutic drug monitoring show that the target trough concentrations are difficult to attain in clinical practice (42)(43)(44)(45). In accordance with reported clinical practice in adults, continu-ous dosing has also been investigated in neonates, infants, and children (31,34,(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…Pediatric evidence and adult consensus recommendations published in 2009 through 2011 suggested that higher starting doses (eg, 60 mg/kg/day) may be necessary to achieve serum trough concentrations corresponding to the optimal area under the curve (AUC) for plasma concentration relative to the organism minimum inhibitory concentration (MIC). [13][14][15] Subsequently, pediatric reports emerged suggesting increased incidence of AKI. 7,8 Relative to data in adults, there are fewer pediatric studies evaluating vancomycin-associated AKI, though similar trends have been observed with respect to AKI-associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence and recommendations suggest that such doses are unlikely to achieve the goal serum trough concentrations (10-20 mg/L) that are necessary for the optimal area under the curve (AUC) for plasma concentration relative to the organism minimum inhibitory concentration (MIC) (AUC/MIC) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%